Energy tangle in china. - Lin-Liu, J.
China, now the world's second largest consumer of electricity, behind the United States power grids are seriously straining, and black outs are becoming more common. Two dozen of China's 31 administrative units had rolling blackouts this year. The problem is worst in the summer, when temperatures of 40 °C are common in some areas. On the hottest days, Chinese officials predict total power demand could top 420 gigawatts, which would mean a shortfall of 30 GW, or twice the estimated deficit in 2003. Although provincial governments are enforcing conservation on industry and scrambling to get power plants built, many observers wonder how the world's most populous country can meet its energy demands.
Keywords: Electricity price; Power demand; Power outage; Power plant; Rolling blackout